Impacts of El NiÃ±o 2015 and the Indian Ocean Dipole 2016 on Rainfall in the Pameungpeuk and Cilacap Regions - Martono, Martono; Wardoyo, Teguh (Forum Geografi, 2017)
El NiÃ±o and the Indian Ocean Dipole (IOD) are oceanographic phenomena which occur in the tropical Pacific Ocean and the Indian Ocean due to airâsea interactions. These phenomena affect climate variability both regionally and globally. This study was conducted to understand the impacts of El NiÃ±o 2015 and IOD 2016 events on rainfall in the Pameungpeuk and Cilacap regions. The data used consists of the NIÃO3.4 index, IOD index, daily rainfall from 1987â2016, daily sea surface temperature from 1987â2016, daily sea surface height from 1994â2016 and pentad sea surface current from 2007â2016. The method used in this research was a descriptive analysis. The results have shown that rainfall in Pameungpeuk and Cilacap was influenced by El NiÃ±o 2015 and negative IOD 2016. During El NiÃ±o 2015 a decrease in rainfall occurred, whereas during negative IOD 2016 rainfall increased. Rainfall anomalies in the east season and the second transition season during El NiÃ±o 2015 in Pameungpeuk reached â107 mm and â374 mm; meanwhile in Cilacap rainfall anomalies reached â111 mm and â218 mm. Conversely, rainfall anomalies during negative IOD 2016 reached 109 mm and 360 mm in Pameungpeuk, and in Cilacap reached 293 mm and 365 mm. Changes in rainfall in Pameungpeuk and Cilacap during El NiÃ±o 2015 and negative IOD 2016 events were closely related to the weakening and strengthening of convections in the southern waters of Java.